Minnesota prairie style: John Howe and the Menomonie public library - Witcher, Diana (University of Wisconsin--Stout. Research Services, 2014)
This paper highlights and analyzes architect John H. Howe’s 1986 design for the Menomonie Public Library, and the preliminary designs leading up to its completion. A prolific Midwest architect in his later career; Howe was Frank Lloyd Wright’s chief draftsman for 27 years. He was known for his speed and proficiency at architectural drawings, which illustrated the profound integration of Wright’s buildings into the landscape. He closely followed Wright’s philosophies and later adapted Prairie School architecture for Minnesota’s unique climate. The Menomonie Public Library illustrates the primary elements found in Howe’s designs. It is based upon a geometric structure and is tailored to suit the characteristic of the site and the needs of the client. Carefully selected natural and modern building materials as well as the surrounding landscape serve as the inspiration for the design. The Menomonie Public library is a unique and functionally beautiful example of organic architecture in the Midwest.
Research article with illustrations.
Keywords: Frank Lloyd Wright; organic architecture; Menomonie Public Library; John H. Howe; Minnesota Prairie School; Organic architecture--Wisconsin--Menomonie; Howe, John H., 1913-1997; Wright, Frank Lloyd, 1867-1959--Influence